The The Role of Baduy Women in Strengthening Baduy Local Food as an Innovation for Food Security in the Banten Region: The Role of Baduy Women in Strengthening Baduy Local Food as an Innovation for Food Security in the Banten Region - Muhamad Muslih; Ahmad Rayhan (Unram Law Review, 2023)
The problem raised in this paper is the role of the Baduy indigenous women in Strengthening Baduy Local Food as an innovation for National Food Security. The purpose of this paper is to strive for the local ecological wisdom of the Baduy indigenous people can be combined with modern science and technology in order to be able to utilize in a sustainable Food Security development program based on National Food Security Innovation. The specific target to be achieved from this research is to examine the field of feminism and gender from the perspective of Baduy women in terms of their relationship to the development of Baduy Local Food Security Innovations. The methodology used is Juridical Normative and Sociological Normative. This research is a descriptive-analytical type of research using Primary and Secondary Data Sources which are analyzed using qualitative methods, applying Library Research and Field Studies data collection techniques toward Inner Baduy and Outer Baduy. Interviews and observations were conducted to obtain the necessary data. The data obtained through field research and literature study were analyzed to obtain clarity on the problems discussed. A brief summary of the results of this paper is that Baduy men and women carry out ngahuma activities and household activities together because the Baduy indigenous people have known and applied the theory of feminism and gender equality. Even in farming, there are ceremonies in which implementation can only be done by Baduy women, such as mipit, ngaseuk, ngalaksa, and nganyaran. In practice, it cannot be done by men because it is directly related to Nyi Pohaci as a symbol of the high degree and honor of women in Baduy. Nyi Pohaci is associated with the symbol of making a living from growing rice in the huma and in the fields. Until now, the Baduy people have always maintained the Baduy pikukuh to store dry unhulled rice produced from ngahuma in Leuit as typical Baduy rice barns. The facts prove that the condition of rice is still good and still very suitable for consumption even though the unhulled rice has been stored in the leuit for more than 50 years. Baduy people are very concerned about life in the future so that their food security can be maintained. If this is analyzed and researched in depth, it can produce a good system to be applied in maintaining Baduy Local Food Security as a reflection of National Food Security.